Does 'race to fish' behaviour emerge in an individual transferable quota fishery when the total allowable catch becomes non‐binding?. Issue 1 (10th January 2013) - Emery, Timothy J; Hartmann, Klaas; Green, Bridget S; Gardner, Caleb; Tisdell, John
Abstract Successful individual transferable quota (ITQ) management requires a binding (constraining) total allowable catch (TAC). A non‐binding TAC may result in a shift back towards open access conditions, where fishers increasingly compete ('race') to catch their share of the total harvest. This process was examined by comparing fishing fleet behaviour and profitability in the Tasmanian southern rock lobster (Jasus edwardsii) fishery (TSRLF), Australia. Between 2008 and 2010, the TSRLF had a non‐binding TAC and effectively reverted to a regulated, limited‐entry fishery. Fishers' uncertainty about future profitability and their ability to take their allocated catch weakened the security characteristic of the ITQ allocation. The low quota lease price contributed to an increase in fleet capacity, while the more limited reduction in quota asset value proved an investment barrier, hindering the autonomous adjustment of quota towards the most efficient fishers. In the TSRLF, catch rates vary more than beach price and are therefore more important for determining daily revenue (i.e., price x catch rate) than market price. Consequently, fishers concentrated effort during times of higher catch rates rather than high market demand. This increased rent dissipation as fishers engaged in competitive race to fish to be the first to exploit the stock and obtain higher catch rates. The history of this fishery emphasizes the need for a constraining TAC in all ITQ fisheries, not only for stock management, but also to manage the security of the ITQ allocation and prevent unanticipated and undesirable changes in fisher behaviour and fishery profitability.